2007
DOI: 10.1021/jp067131s
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Acid−Water Interaction Probed via Isolation in Carbon Tetrachloride

Abstract: The interaction between nitric acid and water is investigated under conditions of limited water activity:  at the aqueous interface and dispersed in the hydrophobic solvent, carbon tetrachloride. It is found that water forms only monomers in carbon tetrachloride at temperatures >0 °C. Addition of nitric acid shows features due to molecular nitric acid and the hydrates:  nitric acid monohydrate (NAM), nitric acid dihydrate (NAD), and nitric acid trihydrate (NAT). Spectral features from water molecules weakly bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…[38][39][40][41][42] However, there are relatively few studies of the interactions of HNO 3 with such surface-bound organics. Shultz and coworkers 43 showed that HNO 3 in CCl 4 was undissociated, while Donaldson and coworkers 4 have shown that HNO 3 adsorbed into an organic film could photodissociate to generate gas phase NO 2 and/or HONO. In this case, the organic acted as a photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40][41][42] However, there are relatively few studies of the interactions of HNO 3 with such surface-bound organics. Shultz and coworkers 43 showed that HNO 3 in CCl 4 was undissociated, while Donaldson and coworkers 4 have shown that HNO 3 adsorbed into an organic film could photodissociate to generate gas phase NO 2 and/or HONO. In this case, the organic acted as a photosensitizer.…”
Section: Introductionmentioning
confidence: 99%
“…The dodecane/water interfacial tension, using the TIP3P water model [36] is also reproduced for the sake of benchmarking (with a value of 51.2 mNm −1 being obtained relative to the experimental value of 50.74 ± 0.08 mNm −1 [37]). In the single-phase system that is the focus of this work, the TIP3P water model [36] was used along with the HNO 3 parameters of [38] which uses the molecular (undissociated) form that is congruent with experimental IR [39] and ab-initio theoretical predictions. [40,18] Additional details regarding the force field parameters are provided in the Supporting Information (see Figure S1, Table S3-S4).…”
Section: Simulation Protocolmentioning
confidence: 99%
“…As part of the benchmarking process we note that the employed parameters reproduce the correct density of 0.1 M TODGA in dodecane as (predicted to be 0.788 gL −1 relative to the experimental value of 0.759 gL −1 33 ), and measured diffusion coefficient 34 (see Results section and Supporting Information). The TIP3P water model 35 was used along with the HNO 3 parameters of Servis et al 21 which uses the molecular (undissociated) form that is congruent with experimental IR 36 and ab initio theoretical predictions. 16,37 Additional details regarding the force field parameters are provided in the Supporting Information (cf.…”
Section: Simulation Protocolmentioning
confidence: 99%